Path Analysis on the Biopsychosocial Factors Affecting the Quality of Life in Patients with Breast Cancer - Rizka Amalia Dewi; Ambar Mudigdo; Eti Poncorini Pamungkasari (Masters Program in Public Health, 2020)
Background: Breast cancer is the most com